Problemy z dyskursem. Czytając Jürgena Habermasa - Smrokowska-Reichmann, Agnieszka (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
The author of the paper presents some critical opinions (including her own) on Habermas'conception of language and discourse. At the same time she strives to explain the maincontroversies which arise from Habermas' key categories. For example Habermas seems tocompare the structure of society with the structure of language, underlining the importance ofcommon practice of speech acts. But is there still any room for such communicative activity in themodern postindustrial world? And, first of all, must we really concentrate all our efforts onpromoting the communicative rationality? The results of universalization principle, as well as theinterrelations between communicative action and discourse (both highlighted in the paper) belongto other problems of Habermas' philosophy. The paper discusses weak points or eveninconsistencies which can be noticed in these conceptions. Finally the author reflects onHabermas' ideal speech situation and on "the utopia touch" in Habermas' seemingly practicalconcepts.